Concordance of in vitro and in vivo measures of non-replicating rotavirus vaccine potency. Issue 34 (12th August 2022) - McAdams, David; Estrada, Marcus; Holland, David; Singh, Jasneet; Sawant, Nishant; Hickey, John M.; Kumar, Prashant; Plikaytis, Brian; Joshi, Sangeeta B.; Volkin, David B.; Sitrin, Robert; Cryz, Stan; et al.
Abstract: Rotavirus infections remain a leading cause of morbidity and mortality among infants residing in low- and middle-income countries. To address the large need for protection from this vaccine-preventable disease we are developing a trivalent subunit rotavirus vaccine which is currently being evaluated in a multinational Phase 3 clinical trial for prevention of serious rotavirus gastroenteritis. Currently, there are no universally accepted in vivo or in vitro models that allow for correlation of field efficacy to an immune response against serious rotavirus gastroenteritis. As a new generation of non-replicating rotavirus vaccines are developed the lack of an established model for evaluating vaccine efficacy becomes a critical issue related to how vaccine potency and stability can be assessed. Our previous publication described the development of an in vitro ELISA to quantify individual vaccine antigens adsorbed to an aluminum hydroxide adjuvant to address the gap in vaccine potency methods for this non-replicating rotavirus vaccine candidate. In the present study, we report on concordance between ELISA readouts and in vivo immunogenicity in a guinea pig model as it relates to vaccine dosing levels and sensitivity to thermal stress. We found correlation between in vitro ELISA values and neutralizing antibody responses engendered after animal immunization. Furthermore, this in vitro assay could be used to demonstrate the effect of thermal stress on vaccine potency, and such results could be correlated with physicochemical analysis of the recombinant protein antigens. This work demonstrates the suitability of the in vitro ELISA to measure vaccine potency and the correlation of these measurements to an immunologic outcome.